Face Perception across the Life-Span - Bozana Meinhardt-Injac (Frontiers Research Topics, 2017)
Face perception is a highly evolved visual skills in humans. This complex ability develops across the life-span, steeply rising in infancy, refining across childhood and adolescence, reaching highest levels in adulthood and declining in old age. As such, the development of face perception comprises multiple skills, including sensory (e.g., mechanisms of holistic, configural and featural perception), cognitive (e.g., memory, processing speed, attentional control), and also emotional and social (e.g., reading and interpreting facial expression) domains. Whereas our understanding of specific functional domains involved in face perception is growing, there is further pressing demand for a multidisciplinary approach toward a more integrated view, describing how face perception ability relates to and develops with other domains of sensory and cognitive functioning. In this research topic we bring together a collection of papers that provide a shot of the current state of the art of theorizing and investigating face perception from the perspective of multiple ability domains. We would like to thank all authors for their valuable contributions that advanced our understanding of face and emotion perception across development.